2016
DOI: 10.1017/s1049023x16000972
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Services Utilization in EMS Priority Conditions in Beirut, Lebanon

Abstract: Emergency Medical Services use in EMS priority conditions in Lebanon is low. Several predictors of EMS use were identified. Emergency Medical Services initiatives addressing underutilization should result from this proposed assessment of the perspective of the EMS system's end user. El Sayed M , Tamim H , Al-Hajj Chehadeh A , Kazzi AA . Emergency Medical Services utilization in EMS priority conditions in Beirut, Lebanon. Prehosp Disaster Med. 2016;31(6):621-627.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…Ambulances were used for transporting 58 (22.7%) of the victims from the scene into the hospital. This is consistent with studies conducted in Lebanon 23% 15 and Addis Ababa, Ethiopia 20%. 17 But, higher as compared to studies conducted in Ghana which showed that the ambulance utilization rate by the general population ranges from 5% to 14.7%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ambulances were used for transporting 58 (22.7%) of the victims from the scene into the hospital. This is consistent with studies conducted in Lebanon 23% 15 and Addis Ababa, Ethiopia 20%. 17 But, higher as compared to studies conducted in Ghana which showed that the ambulance utilization rate by the general population ranges from 5% to 14.7%.…”
Section: Discussionsupporting
confidence: 92%
“…The utilization of EMS in low-income countries ranges from 4% to 23%. 15–18 In these countries, the utilization of EMS was found to be affected by financial problems, lack of awareness, perceived waiting time, misconceptions, use of traditional modes of transportation, prior experience with EMS, and absence of predefined and well-organized EMS. 16 , 17 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] A study from Lebanon reported that functional screening or requiring full assistance was a strong predictor for emergency medical services (EMS) utilization. [ 9 ] Injuries resulting in inability to walk were not common in our study with <18% requiring surgical procedures, explaining low rate of EMS use (14.2%).…”
Section: Discussionmentioning
confidence: 66%
“…A study carried out at the ED of AUBMC showed that only 23.3% of the study population used EMS for all-cause presentations and that EMS use was associated with higher illness severity during routine daily operations. 9 During civil unrest and rioting, however, EMS are expected to increase their readiness by deploying additional ambulances and teams to the conflict zones. Additionally, EMS agencies in Lebanon are well adapted to quick transport and care of trauma-related cases because of the recurrent armed conflicts that occur in the region.…”
Section: Discussionmentioning
confidence: 99%